2022
DOI: 10.1186/s12877-022-03423-7
|View full text |Cite
|
Sign up to set email alerts
|

Dignity and psychosocial related variables in elderly advanced cancer patients

Abstract: Introduction Most cancers occur in older individuals, who are more vulnerable due to functional impairment, multiple comorbidities, cognitive impairment, and lack of socio-familial support. These can undermine patients’ sense of dignity. This study seeks to compare dignity scores in older patients with advanced cancer on sociodemographic and clinical variables and analyze the predictive value of anxiety, depression, functional limitations, and social support on dignity scores. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…There was a significant association between dignity and sex, with male participants more likely to report higher levels of dignity compared to female participants. This finding aligns with previous research on older adults' dignity, which also demonstrated that males tend to report higher levels of dignity than females (Karimi et al, 2019; Martín‐Abreu et al, 2022). This finding may have cultural implications because in most parts of Africa and Asia, men are generally given patriarchal authority as ‘breadwinners’ and heads of the family, while women are subordinated with their roles focussed on domestic chores (Ahmed, 2000; Azuh et al, 2015; Vlassoff, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was a significant association between dignity and sex, with male participants more likely to report higher levels of dignity compared to female participants. This finding aligns with previous research on older adults' dignity, which also demonstrated that males tend to report higher levels of dignity than females (Karimi et al, 2019; Martín‐Abreu et al, 2022). This finding may have cultural implications because in most parts of Africa and Asia, men are generally given patriarchal authority as ‘breadwinners’ and heads of the family, while women are subordinated with their roles focussed on domestic chores (Ahmed, 2000; Azuh et al, 2015; Vlassoff, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…For instance, Karimi et al (2019) found in Iran that dignity was more critical to unemployed individuals than employed individuals, which differs from our findings. Additionally, a study by Martín‐Abreu et al (2022) in Spain revealed significant differences in dignity based on educational level, with individuals with primary education reporting lower dignity levels than those with higher levels of education. These differences in findings may be attributed to variations in data collection instruments and sample characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…Understanding these dynamics provided insights into tailored interventions and support systems [56]. Caregiver-patient relationships within support systems emerged as crucial components in mitigating challenges faced by elderly patients [57,58]. By recognizing and optimizing these relationships, tailored interventions and educational initiatives could be implemented to enhance the well-being of both patients and caregivers [59].…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 It is essential to understand the psychosocial burdens and the concept of dignity because increased hopelessness, depression, and desire to hasten death are associated with the loss of dignity. 16 …”
Section: Dear Editormentioning
confidence: 99%